Hubungan Ego Identity dengan Kecenderungan Perilaku Self Injury pada Siswa - Oktaviani, Lathifa; Taufik, Taufik (MASALIQ, 2025)
The phenomenon in this study is motivated by the large number of students who are less able to build a good ego identity which causes identity confusion, resulting in negative behavior such as self injury. Self-injury is an act of intentionally hurting oneself without the intention of committing suicide, which is generally done to overcome emotional stress or feelings of emptiness. This study aims to describe students' ego identity and self-injury behavior, and the relationship between ego identity and students' self-injury behavior. This study uses a quantitative correlational method. The research sample was 130 students of State Senior High School 1 Sungai Tarab who were selected using the Purposive Sampling technique. The instruments used were an ego identity questionnaire and a self-injury behavior questionnaire. The data were analyzed using the percentage analysis technique and tested using the Pearson Product Moment correlation formula. The results of the study showed that: (1) the average score of students' ego identity achievement reached 91.71 (72.69%) most students had high ego identity, (2) the average score of students' self-injury behavior achievement was 52.42 (35.46%) most students had low self-injury behavior, and (3) there was a significant negative relationship between ego identity and students' self-injury behavior with a correlation of -0.277 and a significance value of 0.001. Thus, it can be interpreted that the higher the student's ego identity, the lower the self-injury, conversely, students with weak ego identity tend to have a higher risk of carrying out this self-injury behavior.